GENETIC ASPECTS IN TRANSMISSIBLE SPONGIOFORM ENCEPHALOPATHIES (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Transmissible spongiform encephalopathy’s (TSE) are a group of infectious neurodegenerative diseases that attack the nerve tissue by creating clusters of prion particles in it. The ultimate outcome of this disease is deadly, and their agent is a prion, a cellular glycoprotein that has two forms, with no infectious α - helix, which is denoted PrPC and infectious, with β - pleated sheet and label PrPSc through. This disease is characteristic of many mammals including man. Studies have shown that there is a genetic predisposition for the disease or resistance to it.